Some case studies of cirriform clouds over India during the winter period - SRINIVASAN, V. (MAUSAM, 1971)
A few cases of extensive formations of upper tropospheric clouds over north and central India during the winter of 1969- 70 were studied utilizing satellite pictures in conjunction with synoptic and upper air charts as well as aircraft reports and hourly observations from airport stations. The ground-observed cloud reports are compared with satellite pictures. The clouds were found to be associated with the jet stream and formed when large amplitude troughs extended into India and neighbourhood. The clouds were also organised in transverse as well as parallel modes; prevailing lapse rates and vertical wind shears have been found to be different in the two modes of organizations.